2015
DOI: 10.1094/php-rs-15-0024
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Bagrada hilaris Density and Feeding Damage in Broccoli: Implications for Pest Management

Abstract: Bagrada hilaris (Burmeister) (Hemiptera:Pentatomidae) has become a serious economic pest of brassica crops in Arizona and southern California. Feeding damage on broccoli can result in excessive seedling mortality and, on established plants, in malformed plants which are not commercially marketable. Although management tactics have been developed for this new pest, a reliable sampling technique for estimating adult density is lacking. Here, we analyzed data from 18 insecticide trials conducted from 2011 to 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…leaf appearance, photosynthetic pigment contents and protective enzyme activities) basically coincided with the threshold that resulted in significant yield loss in the field. Several studies have indicated that plant damage caused by different pest densities could be an early warning signal for pest management intervention . However, without validation by yield loss measurements or before those conventional ‘thresholds’ (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…leaf appearance, photosynthetic pigment contents and protective enzyme activities) basically coincided with the threshold that resulted in significant yield loss in the field. Several studies have indicated that plant damage caused by different pest densities could be an early warning signal for pest management intervention . However, without validation by yield loss measurements or before those conventional ‘thresholds’ (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that plant damage caused by different pest densities could be an early warning signal for pest management intervention. 19,[21][22][23][24][25] However, without validation by yield loss measurements or before those conventional 'thresholds' (i.e. economic injury level, economic threshold and action threshold) were actually confirmed, the threshold determined in the laboratory could only be an early warning rather than a reliable prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This invasive species has colonized numerous regions of the world, with serious effects on brassica crops . The main negative effect of this insect is the damage it causes to plant leaves, reducing chlorophyll generation and leaf area mainly on newer leaf tissues of cotyledons and two‐leaf plants . The species is an important pest in the Old World, mainly India, Africa, Southern Europe, Middle East and Southeast Asia .…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that for the leaf beetle O. communa, and probably other mobile insect herbivores, in-season damage levels may provide a more robust and easier-to-quantify variable for projecting potential impact on reproductive output of A. artemisiifolia at the end of the season. Similarly, early season feeding damage of the bug Bagrada hilaris on broccoli was also found to be a reliable and accurate variable for monitoring this pest in broccoli fields (Palumbo and Carrière 2015). All but one model in which O. communa abundance explained the probability of reproductive organ formation contained an interaction with plant volume.…”
Section: Effect Of In-season O Communa Abundance and Damage On A Armentioning
confidence: 86%